Dutch East India Company Shipbuilding : The Archaeological Study of Batavia and Other Seventeenth-Century VOC Ships - Van Duivenvoorde, Wendy, 1974- (Book collections on Project MUSE., 2015)
WENDY VAN DUIVENVOORDE is a lecturer in maritime archaeology at Flinders University and deputy director of the Australian Consortium of Humanities Research Centres. She is also affiliated faculty with the Institute of Nautical Archaeology at Texas A & M University.